2008
DOI: 10.1175/2007jas2322.1
|View full text |Cite
|
Sign up to set email alerts
|

Subsiding Shells around Shallow Cumulus Clouds

Abstract: In this study large-eddy simulations (LES) are used to gain more knowledge on the shell of subsiding air that is frequently observed around cumulus clouds. First, a detailed comparison between observational and numerical results is presented to better validate LES as a tool for studies of microscale phenomena. It is found that horizontal cloud profiles of vertical velocity, humidity, and temperature are in good agreement with observations. They show features similar to the observations, including the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
168
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(194 citation statements)
references
References 32 publications
26
168
0
Order By: Relevance
“…This can be interpreted either as indicative of strongly inhomogeneous mixing or homogeneous mixing with "environmental" air that is very similar in its thermodynamic properties to the cloud. The latter could be due to, for example, mixing with humid air in subsiding shells (e.g., Heus and Jonker, 2008).…”
Section: Effects Of Differences In Cloud Microphysics On Turbulent MImentioning
confidence: 99%
“…This can be interpreted either as indicative of strongly inhomogeneous mixing or homogeneous mixing with "environmental" air that is very similar in its thermodynamic properties to the cloud. The latter could be due to, for example, mixing with humid air in subsiding shells (e.g., Heus and Jonker, 2008).…”
Section: Effects Of Differences In Cloud Microphysics On Turbulent MImentioning
confidence: 99%
“…Some previous studies have demonstrated clouds' alteration of their environment (Zhao and Austin, 2005;Heus and Jonker, 2008;Malkus, 1954;Lee et al, 2014;Zuidema et al, 2012;Roesner et al, 1990). One example of such an effect is the "preconditioning" or "cloud-deepening" effect (Nitta and Esbensen, 1974;Roesner et al, 1990;Stevens, 2007;Stevens and Seifert, 2008), where clouds cool and moisten the upper cloudy and inversion layers and in this way encourage the development of the next generation of clouds that encounter improved environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(Stevens 2005). A significant portion of cloud research that has occurred has focused on understanding and parameterizing the transport and mixing associated with shallow cumulus and their roots within the subcloud layer (e.g., LeMone and Pennell 1976;Nicholls and LeMone 1980;Nicholls et al 1982;Tiedtke et al 1988;Siebesma 1998;Brown et al 2002;Soares et al 2004;Bellon and Stevens 2005;Zhao and Austin 2005a,b;Stevens 2007;Bretherton and Park 2008;Heus and Jonker 2008;Stechmann and Stevens 2010). However, even though the impact of cumulus convection on surface fluxes has been shown to significantly affect larger-scale circulations (Betts and Ridgway 1988) and the skill of medium-range weather forecasts (Tiedtke 1989), the coupling between shallow cumulus and the land surface deserves further analysis.…”
Section: Introductionmentioning
confidence: 99%